ALS-linked loss of Cyclin-F function affects HSP90 - Siebert, Alexander; Gattringer, Vanessa; Weishaupt, Jochen H.; Behrends, Christian (Life science alliance, 2022)
The founding member of the F-box protein family, Cyclin-F, serves as a substrate adaptor for the E3 ligase Skp1-Cul1-F-box (SCF)Cyclin-F which is responsible for ubiquitination of proteins involved in cell cycle progression, DNA damage and mitotic fidelity. Missense mutations in CCNF encoding for Cyclin-F are associated with amyotrophic lateral sclerosis (ALS). However, it remains elusive whether CCNF mutations affect the substrate adaptor function of Cyclin-F and whether altered SCFCyclin-F-mediated ubiquitination contributes to pathogenesis in CCNF mutation carriers. To address these questions, we set out to identify new SCFCyclin-F targets in neuronal and ALS patient-derived cells. Mass spectrometry-based ubiquitinome profiling of CCNF knockout and mutant cell lines as well as Cyclin-F proximity and interaction proteomics converged on the HSP90 chaperone machinery as new substrate candidate. Biochemical analyses provided evidence for a Cyclin-F-dependent association and ubiquitination of HSP90AB1 and implied a regulatory role that could affect the binding of a number of HSP90 clients and co-factors. Together, our results point to a possible Cyclin-F loss-of-function-mediated chaperone dysregulation that might be relevant for ALS.
Gesehen am 26.06.2023